Islam and Veterinary Science: Rethinking Animal Suffering Through Islamic Animal Ethics and the Evolving Definition of Halal Slaughter - Chao, En-Chieh (Frontiers in Veterinary Science, 2022)
In the midst of recent European activism against religious slaughter, the idea that religious slaughter is cruel to animals is often seen as commonsense, and the mandatory pre-slaughter stunning is often portrayed as the moral technology that assures animal welfare. Nevertheless, this portrayal seems to blur the fact that the current notion of animal welfare itself is built upon a changing selection of value assumptions, which are not without problems or academic debates. It also ignores the fact that contemporary veterinary scientists and Muslim scholars have been working together for four decades to learn more about farm animals and their suffering. Despite stereotypes, the idea of animal ethics is not foreign to Islam. In Islam, animals represent God's wisdom and wonder, and humans are obliged to attend to their health and living conditions. When killing animals for food is conducted, the slaughter must be done in the name of God as a sacred ritual in order to assure that the life of the animal is not taken lightly and that the slaughter is not a sign of hostility toward the universe. Before the act of sacrifice, the animal must be healthy, and no harm should be forced upon it. Accordingly, the requirement of pre-slaughter stunning has posed a question to Muslim scholars: Does stunning kill the animal or cause harm? What defines harm, and whose definition counts? This paper reconstructs a socio-technological history of halal slaughter through scientific research on animal suffering since the 1980s. On the basis of archival research of New Zealand veterinary scientists' works and in-depth interviews with Malaysian veterinary scientists, this article outlines three phases of the evolution of halal slaughter that aims to fulfill multiple sets of moral obligations toward farm animals, and demonstrates how veterinary scientists establish common ground between secular and Islamic animal ethics. In this vein, I am envisioning a possibility of veterinary anthropology that recognizes the field's trans-cultural characteristics, and continues to challenge the rigid binaries between the West and the Rest, and between science and culture.